Kanamycin and Cisplatin Ototoxicity: Differences in Patterns of Oxidative Stress, Antioxidant Enzyme Expression and Hair Cell Loss in the Cochlea - Alejandro Gibaja; Juan C. Alvarado; Verena Scheper; Liliana Carles; José M. Juiz (MDPI AG, 2022)
Kanamycin and cisplatin are ototoxic drugs. The mechanisms are incompletely known. With subcutaneous kanamycin (400 mg/kg, 15 days), auditory threshold shifts were detected at days 12-13 at 16 and 32 kHz, extending to 8 and 4 kHz at days 14-15. The outer hair cell (OHC) loss was concentrated past day 12. The maximum cochlear length showing apoptotic cells, tested with TUNEL, was at day 13. At day 15, 1/5 of the apical cochlea contained preserved OHCs. 3-nitrotyrosine (3-NT) immunolabeling, showing oxidative stress, was found in surviving OHCs and in basal and middle portions of the stria vascularis (SV). The antioxidant Gpx1 gene expression was decreased. The immunocytochemistry showed diminished Gpx1 in OHCs. With intraperitoneal cisplatin (16 mg/kg, single injection), no evoked auditory activity was recorded at the end of treatment, at 72 h. The basal third of the cochlea lacked OHCs. Apoptosis occupied the adjacent 1/3, and the apical third contained preserved OHCs. 3-NT immunolabeling was extensive in OHCs and the SV. Gpx1 and Sod1 gene expression was downregulated. Gpx1 immunostaining diminished in middle and basal SV. More OHCs survived cisplatin than kanamycin towards the apex, despite undetectable evoked activity. Differential regulation of antioxidant enzyme levels suggests differences in the antioxidant response for both drugs.